Analisis Prediksi Potensi Kebangkrutan Pt Indo Asia Sukses Dengan Model Zmijewski Dan Model Springate - Willy Willy (Jurnal Manajemen Bisnis dan Kewirausahaan, 2019)
This research aims to analyze potential bankruptcies of  PT Indo Asia Sukses using Zmijewski and Springate method in period of 2016-2018. The data used is Primary data coming from the company. This research uses qualitative method with two data collections, those are documentation and theoritical study method. The result of research shows that: (1) According to Zmijewski X-Score, the company was in good condition with the negative result in 2016-2018. (2) According to Springate S-Score, the company was in good condition in 2016-2018, but the first quarter of 2017 showed the company had potential to get bankrupt. According to the result of research, it hoped that the company could improve the sales beacuse the research shows that low in sales could get the company bankrupt in first quarter of 2017 and the company could gain more awareness of financial if similar condition happening in the future.